Highlighting the Synergistic Approach against the Antibacterial and Antioxidant Responsiveness of Tartaric Acid-Capped Silver Nanoparticles - Irshad Begum; Sana Shamim (Advanced Concepts in Pharmaceutical Research Vol. 4, 2024)
This chapter outlines a streamlined one-pot synthetic approach for producing silver nanoparticles silver nanoparticles capped with tartaric acid while maintaining a controlled size. Comprehensive characterization using UV/Vis and FTIR spectroscopy, SEM, DLS, and Zetasizer techniques was conducted to unveil key properties of the nanoparticles. The observation of a Surface Plasmon Resonance (SPR) band at 406 nm with 1.07 absorbance units confirmed successful synthesis. SEM images illustrated well-dispersed, spherical particles, and the z-average size distribution in colloidal solution was determined to be 79.20 nm, with a surface charge of -28.2 mV. The antibacterial efficacy of the capped nanoparticles, both independently and in conjunction with fluoroquinolones (Ofloxacin, Sparfloxacin, Ciprofloxacin, and Gemifloxacin) and macrolides (Erythromycin and Azithromycin), were assessed against gram-negative and gram-positive organisms using the disc diffusion method. Antioxidant activity against the DPPH (1, 1-Diphenyl-2-picrylhydrazyl) was also evaluated by the standard assay method. Positive synergistic effects were noted, enhancing the antibacterial activity of antibiotics against studied microorganisms. The study suggests the potential therapeutic application of Tartaric acid-capped silver nanoparticles in combination with antibiotics. Additionally, the capped nanoparticles exhibited noteworthy antioxidant activity, indicating their versatility in biomedical sciences applications.